Absolutely everything! : a history of Earth, dinosaurs, rulers, robots and other things to numerous to mention - Lloyd, Christopher, 1968- (What on Earth Books, 2018)
Presents a full-color illustrated world history of everything from the beginning of the universe to today. Discusses the Big Bang, dinosaurs, ancient civilizations, inventions, world wars, and the modern era.